2001
DOI: 10.2527/2001.7982233x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage:concentrate ratio on ruminal digestion and duodenal flow of fatty acids in ewes.

Abstract: The objective of this study was to determine the forage:concentrate ratio that would provide the greatest duodenal flow of unsaturated fatty acids in ewes supplemented with soybean oil and to determine how diets differing in forage content affect flow of conjugated linoleic acid (CLA) and trans-vaccenic acid (18:1(trans-11)). Five mature ewes (66.5 +/- 12.8 kg) fitted with ruminal and duodenal cannulas were used in a 5 x 5 Latin square experiment. Diets were isonitrogenous and included bromegrass hay, cracked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 11 publications
12
90
2
1
Order By: Relevance
“…Duodenal flows of 18:1 trans isomers in this study are in the same range noted by Lee et al [15]. In studies using sheep, Kucuk et al [11] and Sasaki et al [27] noted an increase in 18:1 trans (vaccenic acid) and a reduction in biohydrogenation with increasing amounts of concentrate and decreasing amounts of forage in the diet. They also found a greater flow of cis 9 trans 11 CLA with increasing forage in the diet.…”
Section: Discussionsupporting
confidence: 88%
“…Duodenal flows of 18:1 trans isomers in this study are in the same range noted by Lee et al [15]. In studies using sheep, Kucuk et al [11] and Sasaki et al [27] noted an increase in 18:1 trans (vaccenic acid) and a reduction in biohydrogenation with increasing amounts of concentrate and decreasing amounts of forage in the diet. They also found a greater flow of cis 9 trans 11 CLA with increasing forage in the diet.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of the diet on absortion of CLA also differs depending on the isomer. For example, Kucuk et al (2001) found that the cis-9, trans-11, the main isomer of CLA present in fat tissue, decreased, while trans-10, cis-12 increased with the addition of concentrate in the diet of the animals. In this study, even though the consumption of polyunsaturated fatty acids was higher in animals that received the conventional diet, duodenal flow of CLA was almost nil in this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It was expected that biohydrogenation would be inhibited in the presence of concentrate in the diet (Kucuk et al, 2001, Loor et al, 2004, which usually causes a decrease in ruminal pH and a decreased lipolysis (Doreau & Ferlay, 1994), which is a prerequisite for biohydrogenation (Latham et al, 1972). Moreover, Loor et al (2004) suggested that changes in microbial population induced by the presence of starch could also adversely affect the ruminal biohydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…We selected the 14 experiments with within-experiment differences in ruminal pH higher than 0.2 units, from which we excluded treatments containing fish oil. There was a concomitant variation of forage : concentrate ratio in three of these 14 experiments (Kalscheur et al, 1997;Kucuk et al, 2001;Harvatine et al, 2002). In this subset, mean pH values varied between 5.5 and 6.6.…”
Section: Digestion Of C18 Fatty Acids In Ruminantsmentioning
confidence: 99%